2020
DOI: 10.3390/ijms21051879
|View full text |Cite
|
Sign up to set email alerts
|

Major Latex Protein MdMLP423 Negatively Regulates Defense against Fungal Infections in Apple

Abstract: Major latex proteins (MLPs) play critical roles in plants defense and stress responses. However, the roles of MLPs from apple (Malus × domestica) have not been clearly identified. In this study, we focused on the biological role of MdMLP423, which had been previously characterized as a potential pathogenesis-related gene. Phylogenetic analysis and conserved domain analysis indicated that MdMLP423 is a protein with a ‘Gly-rich loop’ (GXGGXG) domain belonging to the Bet v_1 subfamily. Gene expression profiles sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 57 publications
(51 reference statements)
0
21
0
Order By: Relevance
“…Its function to fungal invasion is still unclear. Recently, in an RNAseq study of fungus–apple interaction, one MLP gene was found to impact a handful of defense-related genes including transcription factors (He et al 2020 ). It seems that MLP genes play important roles for defense in many crops including sugar beet; details of their function remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Its function to fungal invasion is still unclear. Recently, in an RNAseq study of fungus–apple interaction, one MLP gene was found to impact a handful of defense-related genes including transcription factors (He et al 2020 ). It seems that MLP genes play important roles for defense in many crops including sugar beet; details of their function remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, functionality of this candidate gene can be inferred from previous functional characterization studies of MLP-like protein-encoding genes, which have demonstrated the critical role of this gene family as a positive regulator of plant defense against fungal infection in upland cotton (Gossypium hirsutum L.) (Yang et al, 2015) and apple [Malus domestica (Suckow) Borkh.] (He et al, 2020). Therefore, the colocalization of the Glyma.15G217100 gene with the peak SNP and the variation of its expression level induced by P. sojae in the PIs carrying the R allele make this gene an interesting candidate.…”
Section: Discussionmentioning
confidence: 99%
“…The last defense-associated protein found to be upregulated in the O 3 -exposed fruits inoculated with B. cinerea was the MLP. MLP and the orthologs of MLP (MLP-like protein) belong to the PR10 family and have been found in several plant species, including apple, and most of them are expressed during fruit ripening ( He et al, 2020 ; Song et al, 2020 ). Although the precise molecular basis of protection of plants by MLPs against plant pathogens currently is unclear, evidence has been provided for their induction on several plant hosts against a wide range of plant pathogens such as fungi, viruses, and phytoplasmas ( Segarra et al, 2013 ; Yang et al, 2015 ; Gai et al, 2018 ; Song et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%